Critical Discourse Analysis Of Susilo Bambang Yudhoyono’s Speech - Risadi, Md. Yudyantara; Ariputra, Putu Suyasa; Premananda, Ni Luh Putu Uttari; Nuriawan, I Nengah Alit (International Journal of Linguistics and Discourse Analytics, 2021)
This study aimed at descrsibing language, power and ideology of SBY’s speech about receiving Doctor Honoris Cause degree from SOKA University, Japan. In someone’s speech, there is a relationship among language, power, and ideology which can be seen through the language use by the speaker. The analysis used was Critical Discourse Analysis method presented by Thomas N. Huckin. It was started form analyzing the features in the text as whole, in sentence-level, word-level and it was continued by doing contextual interpretation. The result showed that through the language use in SBY’s speech, there was a power and the purpose of the speaker in which the power was felt to increase from the beginning, it was felt a weak power and in the middle of the speech it was felt a strong power. The power was increased because it was based on who was aimed at and the ideology is clearly seen in the last part of the speech given in which SBY wanted to be more appreciated